Effect of Reperfusion Therapies on Incidence of Early Post-Stroke Seizures - Mushannen, Tasnim; Aleyadeh, Rozaleen; Siddiqui, Maria; Saqqur, Maher; Akhtar, Naveed; Mesraoua, Boulenouar; Al Jerdi, Salman; Melikyan, Gayane; Shaheen, Yanal; Qadourah, Haneen; Chagoury, Odette; Mahfoud, Ziyad R.; et al. (Frontiers in Neurology, 2021)
Objective: This study aimed to determine the effect of reperfusion therapies on the occurrence of early post-stroke seizures (PSS) in patients with acute ischemic stroke (AIS). Background: Reperfusion therapies are paramount to the treatment of stroke in the acute phase. However, their effect on the incidence of early seizures after an AIS remains unclear. Design and Methods: The stroke database at Hamad Medical Corporation was used to identify all patients who received reperfusion therapies for AIS from 2016 to 2019. They were matched with patients of similar diagnosis, gender, age, and stroke severity as measured by National Institutes of Health Stroke Scale (NIHSS) who did not receive such treatment. The rates of early PSS were calculated for each group. Results: The results showed that 508 patients received reperfusion therapies (342 had IV thrombolysis only, 70 had thrombectomies only, and 96 had received both), compared with 501 matched patients receiving standard stroke unit care. Patients who received reperfusion therapies were similar to their matched controls for mean admission NIHSS score (9.87 vs. 9.79; p = 0.831), mean age (53.3 vs. 53.2 years; p = 0.849), and gender distribution (85 vs. 86% men; p = 0.655). The group receiving reperfusion therapies was found to have increased stroke cortical involvement (62 vs. 49.3%, p < 0.001) and hemorrhagic transformation rates (33.5 vs. 18.6%, p < 0.001) compared with the control group. The rate of early PSS was significantly lower in patients who received reperfusion therapies compared with those who did not (3.1 vs. 5.8%, respectively; p = 0.042). When we excluded seizures occurring at stroke onset prior to any potential treatment implementation, the difference in early PSS rates between the two groups was no longer significant (2.6 vs. 3.9%, respectively; p = 0.251). There was no significant difference in early PSS rate based on the type of reperfusion therapy either (3.2% with thrombolysis, 2.9% with thrombectomy, and 3.1% for the combined treatment, p = 0.309). Conclusions: Treatment of AIS with either thrombectomy, thrombolysis, or both does not increase the risk of early PSS.